COMPRESSION SYNDROMES AS INCIDENTAL FINDINGS DURING MULTISLICE COMPUTED TOMOGRAPHY OF ABDOMINAL ORGANS AND RETROPERITONEAL SPACE - Zh. S. Mel’nichenko; M. V. Vishnyakova (Вестник рентгенологии и радиологии)
Objective.To estimate the clinical significance of compression syndromes accidentally detected by multislice computed tomography (MSCT) of the abdominal cavity and retroperitoneal space.Material and methods. Intravenous bolus contrast-enhanced MSCT study was performed in 645 patients with different diseases of the abdominal cavity and retroperitoneal space. The information obtained after analysis of diagnostic images was compared with clinical symptoms and, in some cases, with intraoperative data.Results. MSCT study identified prerequisites for the occurrence of compression syndromes in 71 (11%) patients of the study group, of whom 11 (15%) patients were noted to have relevant clinical manifestations. Surgical treatment was performed in 3 cases; medical treatment proved to be effective in the remaining 8 cases.Conclusion. Compression syndromes were diagnosed in 11 (1.7%) of the 645 patients examined by MSCT for different diseases of the abdominal cavity and retroperitoneal space. Their timely and adequate diagnosis could rule out other diseases with similar clinical manifestations and define optimal tactics.